Community Participation in Village Development Planning: Partisipasi Masyarakat dalam Perencanaan Pembangunan Desa - Nadhiro, Riza Ayu; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates community participation in planning physical development in Suko Village, Sidoarjo District, Indonesia. Employing descriptive qualitative research, the study utilizes interviews, observation, and documentation, with purposive sampling techniques. The results reveal a five-stage model of community involvement: (1) establishment of the Suko Village RPJM drafting team, (2) hamlet meetings, (3) community participation in village development planning, (4) preparation of plans and development plans for community involvement (BPD), and (5) establishment of the Village RPJM, represented by the BPD. This study contributes to the understanding of community participation in development planning and offers insights for enhancing community involvement in urban and rural settings. Highlight : Five-stage model: Identifies key stages for community involvement in physical development planning. Purposive sampling: Ensures diverse stakeholder voices are heard during planning process. BPD representation: Empowers village representatives to champion community needs in development plans. Keywords: community participation, physical development, Suko Village, Indonesia, qualitative research